A dehydrin gene isolated from feral olive enhances drought tolerance in Arabidopsis transgenic plants - Chiappetta, Adriana; Muto, Antonella; Bruno, Leonardo; Woloszynska, Magdalena; Van Lijsebettens, Mieke; Bitonti, Maria B. (Frontiers in Plant Science, 2015)
Dehydrins belong to a protein family whose expression may be induced or enhanced by developmental process and environmental stresses that lead to cell dehydratation. A dehydrin gene named OesDHN was isolated and characterized from oleaster (Olea europaea L. subsp. europaea, var. sylvestris), the wild form of olive. To elucidate the contribution of OesDHN in the development of drought tolerance, its expression levels were investigated in oleaster plants during development and under drought stress condition. The involvement of OesDHN in plant stress response was also evaluated in Arabidopsis transgenic lines, engineered to overexpress this gene, and exposed to a controlled mild osmotic stress. OesDHN expression was found to be modulated during development and induced under mild drought stress in oleaster plants. In addition, the Arabidopsis transgenic plants showed a better tolerance to osmotic stress than wild-type plants. The results demonstrated that OesDHN expression is induced by drought stress and is able to confer osmotic stress tolerance. We suggest a role for OesDHN, as a putative functional marker of plant stress tolerance.